FACTORS OF MANAGING THE SYSTEM OF WORKING WITH YOUTH IN HIGHER EDUCATION AS AN EXAMPLE OF FOREIGN EXPERIENCES (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
It is important to manage the system of working with youth in higher education, increase the efficiency of educational institutions and ensure the development of students. Foreign experiences provide interesting examples in this regard and help to identify the governing factors. Strategic planning in higher education institutions is an important factor in managing the youth work system. For example, universities in the United States use their strategic plans to identify student needs and develop educational programs that meet them.